Misinterpretation of online surgical outcomes: The British Association of Urological Surgeons Surgical Outcomes Audit. (May 2019) - Sathianathen, Niranjan J; Albersheim-Carter, Jacob; Labine, Lucas; Watson, Brett; Konety, Badrinath R; Weight, Christopher J
Objective: The purpose of this study was to evaluate whether the information presented in the British Association of Urological Surgeons Surgical Outcomes Audit is comprehended by the general population. Methods: An in-person electronic survey was administered at the local state fair in 2016. Participants were presented with an representative output from the British Association of Urological Surgeons Surgical Outcomes Audit and were asked to estimate the complication rate and make a hypothetical healthcare decision. The primary output depicted a complication rate of 6.7% which was above the 99 th percentile. The degree of misinterpretation and the risk of making an inappropriate healthcare decision was evaluated. Results: Of the 350 completed responses, only 142 (40.6%) correctly estimated the surgeons' complication rate. Individuals who were not college educated (odds ratio 3.02, 95% confidence interval 1.88–4.95) were more likely to misinterpret the information. Only 7.6% recognized that the surgeon's complication rate was above the 99 th percentile. Despite the high complication rate, 16.6% decided to continue with the surgery as planned and not ask the surgeon about their rates, seek a second opinion or change surgeons. Misinterpreters had a higher risk of making an inappropriate hypothetical decision (odds ratio 2.75, 95% confidence interval 1.42–5.62). Conclusion: The general population have difficulty in interpreting the data presented by The British Association of Urological Surgeons Surgical Outcomes Audit and are thus vulnerable to making poor healthcare decisions or decisions which are inconsistent with their goals of care. Level of evidence: IIb